2019
DOI: 10.3748/wjg.v25.i44.6561
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pancreatitis and the heart disease: Still terra incognita?

Abstract: BACKGROUNDIt has been suggested that chronic pancreatitis (CP) may be an independent risk factor for development of cardiovascular disease (CVD). At the same time, it seems that congestive heart failure (CHF) and CP share the responsibility for the development of important clinical conditions such as sarcopenia, cachexia and malnutrition due to development of cardiac cachexia and pancreatic exocrine insufficiency (PEI), respectively.AIMTo explore the evidence regarding the association of CP and heart disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
8
0
6
Order By: Relevance
“…-Cálculos en el conducto pancreático 5 (27,8) -Dilatación del conducto pancreático 5 (27,8) RMN o CPRM 24 (29,6) -Cálculos en la vía biliar 4 (16,7)…”
Section: Resultsunclassified
“…-Cálculos en el conducto pancreático 5 (27,8) -Dilatación del conducto pancreático 5 (27,8) RMN o CPRM 24 (29,6) -Cálculos en la vía biliar 4 (16,7)…”
Section: Resultsunclassified
“…So far, research on association between heart and pancreas disease has been paid little attention and its role in pathogenesis is not fully elucidated. The pathogenesis could be pancreatic enzymes and their inhibitors that profoundly affected blood coagulation and appear to in uence the course of pancreatic in ammation [59]. Researches have shown that in patients with chronic heart failure, the splanchnic circulation is decreased, especially in highly vascularized pancreas , which may cause pancreatitis [60].…”
Section: Discussionmentioning
confidence: 99%
“…14,30 Whereas correlations with pancreatitis have been proposed, no consensus exists. 27 We propose here a new hypothesis and provide initial evidence for a fundamental pathogenic mechanism that involves digestive enzymes.…”
Section: Introductionmentioning
confidence: 91%